BRAFV600E mutation and its association with clinicopathological features of colorectal cancer: a systematic review and meta-analysis. - Dong Chen; Jun-Fu Huang; Kai Liu; Li-Qun Zhang; Zhao Yang; Zheng-Ran Chuai; Yun-Xia Wang; Da-Chuan Shi; Qing Huang; Wei-Ling Fu (PLoS ONE, 2014)
Background Colorectal cancer (CRC) is a heterogeneous disease with multiple underlying causative genetic mutations. The B-type Raf proto-oncogene (BRAF) plays an important role in the mitogen-activated protein kinase (MAPK) signaling cascade during CRC. The presence of BRAFV600E mutation can determine the response of a tumor to chemotherapy. However, the association between the BRAFV600E mutation and the clinicopathological features of CRC remains controversial. We performed a systematic review and meta-analysis to estimate the effect of BRAFV600E mutation on the clinicopathological characteristics of CRC. Methods We identified studies that examined the effect of BRAFV600E mutation on CRC within the PubMed, ISI Science Citation Index, and Embase databases. The effect of BRAFV600E on outcome parameters was estimated by odds ratios (ORs) with 95% confidence intervals (CIs) for each study using a fixed effects or random effects model. Results 25 studies with a total of 11,955 CRC patients met inclusion criteria. The rate of BRAFV600 was 10.8% (1288/11955). The BRAFV600E mutation in CRC was associated with advanced TNM stage, poor differentiation, mucinous histology, microsatellite instability (MSI), CpG island methylator phenotype (CIMP). This mutation was also associated with female gender, older age, proximal colon, and mutL homolog 1 (MLH1) methylation. Conclusions This meta-analysis demonstrated that BRAFV600E mutation was significantly correlated with adverse pathological features of CRC and distinct clinical characteristics. These data suggest that BRAFV600E mutation could be used to supplement standard clinical and pathological staging for the better management of individual CRC patients, and could be considered as a poor prognostic marker for CRC.